Case report: Abrikossoff's tumor of the facial skin - Ardeleanu, Valeriu; Jecan, Radu Cristian; Moroianu, Marius; Teodoreanu, Razvan Nicolae; Tebeica, Tiberiu; Moroianu, Lavinia Alexandra; Bujoreanu, Florin Ciprian; Nwabudike, Lawrence Chukwudi; Tatu, Alin Laurentiu (Frontiers in Medicine, 2023)
Abrikossoff tumors, also known as granular cell tumors (GCT), originate from Schwann cells. The most common location is in the oral cavity, followed by the skin, but they can also be found in the breast, digestive tract, tracheobronchial tree, or central nervous system. They can affect both sexes at any age, with a higher incidence between 30 and 50 years and a slight predisposition for female sex. They are usually solitary tumors but may also be multifocal. Most of the time, they are benign, with malignancy being exceptional in <2% of cases. Clinically, they appear as solid, well-defined, painless tumors, located subcutaneously with dimensions that can reach up to 10 cm. The definitive diagnosis is based on the immunohistochemical examination, and the treatment for benign tumors consists of surgical excision. Chemotherapy or radiotherapy may be required for malignant lesions, but the treatment regimens and their benefits remain unclear. This manuscript presents the case of a 12-year-old girl with a benign GCT, located in the skin on the mandibular line.